Free Indirect Discourse. German and Russian Literature (ENTHYMEMA, 2025)
The paper first gives a definition of free indirect discourse (FID) and then characterizes the two main directions of its research. The more traditional one, is based on the application of the three modes of speech representation to the representation of characters' minds (direct, indirect, and free indirect discourse). The text interference model is an alternative to the tripartite approach. It goes back to Mixail Baxtin's description of FID as a "hybrid construction" that "contains mixed within it two utterances, two speech manners, two styles, two 'languages', two semantic and axiological belief systems". The following essay examines the development of free indirect discourse (FID) in German and Russian literature.
Keywords: Free Indirect Discourse; Three Modes of Speech Representation; Text Interference Model